MODERN APPROACH TO THE TREATMENT OF ALLERGIC RHINITIS IN CHILDREN - Bobokulova D.F. (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: аmong the topical issues of modern allergology, the problem of allergic rhinitis (AR) in children has a special place . Allergic rhinitis is one of the common allergic diseases of childhood. This disease is a global problem, because it has a high specific place in allergic pathology (60-70%) and is also common in children's population (10-15%), which emphasizes the importance of the problem.